Purchase Decisions on Rockland Bogor Convection T-Shirts - Masayu, Baby Panca; Maulana, Lucky Hikmat; Yulianingsih; Andari, Titiek Tjahja (International Journal of Managemen Analytics (IJMA), 2023)
This study aims to analyze and identify the effect of price perceptions and promotions simultaneously or partially on purchasing decisions of Rockland Screen Printing Convection T-Shirts. Questionnaires were distributed to 60 respondents using purposive sampling technique with the following criteria; 1) consumers have purchased Rockland Screen Printing products at least 2 times, 2) consumers are at least 17 years old. Data collection was carried out through a questionnaire. The analytical method uses descriptive and verification methods through multiple correlation, multiple regression, coefficient of determination, F test and t test. The results showed that the perceived price and promotion variabels simultaneously or partially had a positive and significant effect on the purchasing decision of the Rockland Screen Printing Convection T-Shirt.